Relevant Aspects of Centrifugation Step in the Preparation of Platelet-Rich Plasma. (25th March 2014) - Perez, Amanda G. M.; Lana, José Fábio S. D.; Rodrigues, Ana Amélia; Luzo, Angela Cristina M.; Belangero, William D.; Santana, Maria Helena A.
Abstract : Introduction . Platelet-Rich Plasma (PRP) is rich in growth factors, playing important role in tissue healing. The wide variation of reported protocols for preparation of PRP leads to variable compositions, which induce different biological responses and prevent results comparison. This study aims to highlight relevant aspects of the centrifugation step to obtain reproducible results and overall quality. Material and Methods . Samples of blood were collected from 20 healthy donors that have signed free informed consent. Two centrifugation steps (spins) were analyzed for the influence of centrifugal acceleration, time, processed volume, and platelet gradient. The Pure Platelet-Rich Plasma (P-PRP) was characterized as platelet concentration, integrity, and viability (sP-selectin measurement). Results . Lower centrifugal accelerations favour platelet separation. The processing of 3.5 mL of blood at 100 ×g for 10 min (1st spin), 400 ×g for 10 min (2nd spin), withdrawing 2/3 of remnant plasma, promoted high platelet recovery (70–80%) and concentration (5x) maintaining platelet integrity and viability. The recovery of platelets was reduced for a larger WB volume (8.5 mL) processed. Conclusion . Centrifugal acceleration, time, WB processed volume, and minimization of the platelet gradient before sampling are relevant aspects to ensure reproducible compositions within the autologous nature of PRP.